O conceito de função em livros didáticos do novo ensino médio - SILVA, Frederico Carvalho da (2022)
The present study presents, as main focus, a discussion on the concept of function brought by the textbooks of the “New High School” approved by public schools in the country in the PNLD of 2021 program. academically and for society, a research was carried out in three mathematics textbooks of the New High School, in order to analyze how the subject is introduced to high school students. The analysis was based on the needs mentioned in the National Curricular Common Base (BNCC) and making a connection with the Theory of Meaningful Learning (TAS). During the work, it was possible to perceive the relevance of analyzing a textbook, since it is one of the main tools used in the classroom, which aims to facilitate the teaching process and the learning process. By not being in agreement with the objectives outlined by the teacher, distancing itself from the teaching proposal and limiting the possibilities of exploring the concepts, the textbook may not fulfill its role of supporting the teacher and the student in the teaching process and learning. For the study, a qualitative approach was used to analyze the definitions, representations, exemplifications and approaches to the theme, presenting considerations and conclusions regarding the referred subject.